1979
DOI: 10.1104/pp.63.5.956
|View full text |Cite
|
Sign up to set email alerts
|

Low Root Temperature Effects on Soybean Nitrogen Metabolism and Photosynthesis

Abstract: The influences of low root temperature on soybeans (Glycine max IL.1Merr. cv. Wells) were studied by germinating and maintaining plants at root temperatures of 13 and 20 C through maturity. At 42 days from the beginning of imbibition, 13 and 20 C plants were switched to 20 and 13 C, respectively. Plants were harvested after 63 days. Control plants (13 C) did not nodulate, whereas those switched to 20 C did and at harvest had C2H2 reduction rates of 0.2 micromoles per minute per plant. Rates of C2H2 reduction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…In fact, the benefit of legumes to the growth of associated grass varies depending on both legume and grass species (Ta and Fails, 1987a). On the other hand, environmental variations, which are also known to affect NF (Feigenbaum and Mengel, 1979;Harding and Sheeley, 1980;Schweitzer and Harper, 1980;Wahua and Miller, 1978), N assimilation (Duke et al, 1979, Duke andDoehlert, 1981) and N excretion (Taet al, 1986;Virtanen et al, 1937) by legumes, would therefore also affect NT. Wyss and Wilson (1937) suggested that the relationship between photosynthesis and NF as affected by environmental conditions may be the dominant factor controlling N excretion.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, the benefit of legumes to the growth of associated grass varies depending on both legume and grass species (Ta and Fails, 1987a). On the other hand, environmental variations, which are also known to affect NF (Feigenbaum and Mengel, 1979;Harding and Sheeley, 1980;Schweitzer and Harper, 1980;Wahua and Miller, 1978), N assimilation (Duke et al, 1979, Duke andDoehlert, 1981) and N excretion (Taet al, 1986;Virtanen et al, 1937) by legumes, would therefore also affect NT. Wyss and Wilson (1937) suggested that the relationship between photosynthesis and NF as affected by environmental conditions may be the dominant factor controlling N excretion.…”
Section: Introductionmentioning
confidence: 97%
“…cv. Wells) (Duke et al 1979), ryegrass (Lolium multiflorum and Lolium perenne) (Clarkson and Warner 1979), arctic plant species (Atkin and Cummins 1994), Eucalyptus nitens (Deane and Maiden) Maiden (Garnett and Smethurst 1999), and rose (Rosa  hybrida cv. Grand Gala) plants (Calatayud et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Trimmed plants were either potted and maintained in a greenhouse or washed, wrapped in wet cheesecloth and plastic, and stored at -2°C until use. Greenhouse-grown plants were inoculated with a mixture of Rhizobium meliloti strains (Nitragen Co., Milwaukee, WI) and irrigated with a nitrogen-free nutrient solution (9).…”
mentioning
confidence: 99%